2022
DOI: 10.1002/anie.202204378
|View full text |Cite
|
Sign up to set email alerts
|

Sigmatropic [1,5] Carbon Shift of Transient C3 Ammonium Enolates

Abstract: The stereospecific sigmatropic [1,5] carbon shift of C3 ammonium enolates is discovered. According to mechanistic, kinetic and computational experiments, this new rearrangement proceeds via the catalytic generation of a transient C3 ammonium enolate by intramolecular aza-Michael addition. This intermediate rapidly undergoes [1,5] sigmatropic carbon migration to furnish the respective tetrahydroquinoline-4-ones with excellent diastereoselectivities of d.r. > 99 : 1 and in 61-98 % yield.Rearrangement reactions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…However, during our mechanistic studies, we found that the enantiopure N-methyl-N-phenylethyl derivative 52a was converted to the product 53a with stereospecific migration of the phenylethyl moiety (Scheme 15a). 64 We concluded that the exceptional enantio-and diastereoselectivity must arise from a concerted [1,5] carbon shift. Kinetic experiments and quantum chemical calculations fully support this picture of a sigmatropic [1,5] carbon shift via transiently formed C3 ammonium enolates.…”
Section: Flp-catalyzed Reactionsmentioning
confidence: 86%
See 1 more Smart Citation
“…However, during our mechanistic studies, we found that the enantiopure N-methyl-N-phenylethyl derivative 52a was converted to the product 53a with stereospecific migration of the phenylethyl moiety (Scheme 15a). 64 We concluded that the exceptional enantio-and diastereoselectivity must arise from a concerted [1,5] carbon shift. Kinetic experiments and quantum chemical calculations fully support this picture of a sigmatropic [1,5] carbon shift via transiently formed C3 ammonium enolates.…”
Section: Flp-catalyzed Reactionsmentioning
confidence: 86%
“…The quinolinones 51a – o were obtained in good to high yields, mostly as cis diastereomers. However, during our mechanistic studies, we found that the enantiopure N -methyl- N -phenylethyl derivative 52a was converted to the product 53a with stereospecific migration of the phenylethyl moiety (Scheme a) …”
Section: Flp-catalyzed Reactionsmentioning
confidence: 99%
“…The Stevens rearrangement is typically applied to construct complex nitrogen/sulfur-containing compounds through [1,2]- or [2,3]-sigmatropic rearrangement, starting from ammonium or sulfonium salts. However, harsh conditions, such as the presence of a strong base, are usually necessary and unavoidable, and the key intermediate is nitrogen 6 14 or sulfur 15 19 ylide. Therefore, Stevens rearrangement is often considered a commonly used molecular editing method for prevalent tertiary amines.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Zhang and coworkers demonstrated a 5-endo-dig cyclization of tertiary amines with intramolecular alkynes activated by π-Lewis-acid to form quaternary ammonium salts, then render nitrogen ylides 41 . However, the universalities of the known Stevens rearrangements are quite poor, usually it is difficult for them to be compatible with all allyl, propargyl, and benzyl groups in one reaction under the same conditions 6 14 , which thus restricts the derivation of product diversity. Consequently, studies toward the efficient and versatile methods for both [1,2]- and [2,3]-Stevens rearrangements are highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the cascade [1, n ]-hydride transfer/cyclization strategy, 4 namely a “redox-neutral process”, has distinguished itself from other C–H bond functionalization approaches in amines 5 due to its fascinating advantages for the straightforward construction of various heterocycles, which feature redox-neutrality and inherent high step- and atom-economy. Remarkably, some intolerable disadvantages of this protocol still persist, e.g.…”
Section: Introductionmentioning
confidence: 99%